DISCOVERING THE WORLD LANDSCAPE OF MICROCREDIT AND WOMEN’S DECISION MAKING: A BIBLIOMETRIC ANALYSIS - Nurul Hayani Abd Rahman; Zuraidah Mohamed Isa; Azyyati Anuar (International Journal of Accounting, Finance and Business, 2023)
This paper aims to examine the current trend and academic growth of microcredit and women's decision-making using bibliometric analysis. This paper also analyses document type, sources of publication, authorship, and other bibliometric indicators. The study focused on a total of 310 articles published from 1999 to 2021. These papers were obtained automatically from the Scopus database and analysed afterward with the use of Harzing’s Publish or Perish and VOSviewer. The result shows that 2021 had the highest productivity with a total of 50 documents produced, whereas 1999 and 2001 had the lowest productivity with a total of one document produced.